Skip-beat! 16 - Nakamura, Yoshiki (Shojo beat manga., 2009)
Saving Kyoko from Reino's attack has finally knocked some sense into Sho's head, and he realizes how much he cares for her. But before he can declare his devotion, Ren shows up to ruin the moment. Both men realize that Kyoko has no idea of their true feelings for her and begin a secret battle for her affections.